Common law, charity, and human rights as responses to the socio-economic crisis in Galicia, Spain - Aguiar Fernández, Francisco Xabier; Verde Diego, Carmen; Prado Conde, Santiago (Journal of Sociology and Social Welfare, 2018)
This article presents the findings of a research project analyzing the effects of the Spanish socio-economic crisis on rural areas. It describes the perceptions of social workers in the public sector engaged in community practice and the perceptions of social leaders working for public and private human service organizations within the province of Ou-rense, Spain. It explores how the current economic crisis has affected people, health care units and the social workers’ scope of action. The study relied on secondary data, surveys and qualitative interviews. Study findings suggest that the adopted measures for responding to the effects of the crisis have been scarce. The primary responses to the crisis include privatization of human services and the transfer of responsibility from government to civil society organizations. Instead of focusing on charity, this study in Galicia, Spain proposes a greater focus on rural social work and on the promotion and defense of human rights by civic and other organizations.
Keywords: crisis; human rights; rural areas; social services; social work; Scopus